Antimicrobial Resistance of Coagulase-Positive Staphylococcus Isolates Recovered in a Veterinary University Hospital - Marta Pérez-Sancho; Sergio Alvarez-Perez; Teresa Garcia-Seco; Marta Hernandez; David Rodríguez-Lázaro; Lucas Domínguez; Marta Eulalia García; Jose Luis Blanco (MDPI AG, 2020)
The Staphylococcus pseudintermedius group (SIG) is an emerging threat in veterinary medicine, particularly methicillin-resistant (MRSP) isolates, which are frequently associated with multidrug resistance. Reliable identification of SIG members is critical to establish correct antimicrobial treatments. However, information on the molecular epidemiology and antimicrobial resistance patterns of MRSP in some regions is still limited. This study aimed to assess the antimicrobial resistance of SIG isolates recovered from animals at the Veterinary Teaching Hospital of Complutense University of Madrid (Spain) during a 10-year period (2007-2016). A total of 139 selected Staphylococcus isolates were subjected to species-level identification by different bioanalytical techniques (PCR, VITEK, MALDI-TOF) and subsequent antimicrobial susceptibility testing. Methicillin-resistant isolates (n = 20) were subjected to whole genome sequencing for further characterization of their antibiotic resistance determinants. Our results showed that there was a good correlation between PCR and MALDI-TOF identification, whereas VITEK showed very divergent results, thus confirming MALDI-TOF as a good alternative for species-level identification of coagulase-positive staphylococci. Notably, S. pseudintermedius, including the epidemic MRSP genotype ST71, was the only SIG species found among canine isolates. In addition, we found a high prevalence of multidrug resistance and resistance to fluoroquinolones, cephalosporins and macrolides. Finally, diverse genes associated with antibiotic resistance were detected among MRSP isolates, although the genetic basis of some of the resistant phenotypes (particularly to fluoroquinolones) could not be determined. In conclusion, our study reveals the circulation of MRSP in the veterinary setting in Spain, thus highlighting the emerging threat posed by this bacterial group and the need for further epidemiological surveillance.